Progress testing and its effect on medical student motivation - Bulan Kakanita Hermasari; Dimar Yudistyaningrum (Intelektual Pustaka Media Utama, 2021)
Assessment has a pivotal role in medical education, as it can direct student learning. Motivation is an essential factor that determines learning assessment results. One of the aims of assessment is to determine the level of student knowledge, one of which can be measured by a progress test. This study aimed to determine the relationship between progress test and student motivation. This study used a cross-sectional observational analytic method. It was conducted in 2017 at Faculty of Medicine Universitas Sebelas Maret (FM UNS), Indonesia. The respondents consisted of 253 students from batch 2014, 2015, and 2016. The sample was selected by stratified random sampling. The instrument used to assess academic motivation was the academic motivation scale (AMS). The research data were analyzed using the Pearson correlation test. There is a significant positive correlation between progress test results and academic motivation (r=0.500; p=0.000). However, there is no significant difference in motivation level based on gender (p=0.889) and student cohort (p=0.533). In the progress test score, there are significant differences based on gender (p=0.014) and grade-point average (p=0.000). However, there is no significant difference in the progress test scores based on the student batch (p=0.212). The results support that progress test is useful assessment method to support medical student’s motivation.